Pick the equation for which it is easier to "isolate" one of the variables.
A) from the second: x = 6+y
plug that into the first
3x + y = 8
3(6+y) + y = 8
18 + 3y + y = 8
4y = -10
y = -5/2
now put that back into the easier of the two
x = 6+y
x = 6 - 5/2 = 7/2
b) really easy, y is already isolated
c) notice we have 2y isolated , but 2y shows up in the first, so again, real easy
x + 2y = 9
x + (-x + 13) = 9
13 = 9 ?????
ahhh, this last pair of equation has no solution, (we got a silly statement)
A. 3x + y = 8
x-y =6
B. x- 1/2y =2
y=2x-4
C. x + 2y = 9
2y = -x + 13
I am not grasping the substitution method! Please help me.
1 answer